War and Peace. Debates on the construction of the civic center in Brasília - Frajndlich, Rafael Augusto Urano de Carvalho; Benoit, Alexandre Hector (Risco - Journal of Architecture and Urbanism, 2023)
The discussions on the Civic Center of the New Capital of Brazil stretches an arc from the Technical Board post-Belcher Plant in 1954 to the Square of Three Powers, designed by Oscar Niemeyer and Lucio Costa in 1957. It is larcenous the establishment of connections between the architecture of the Civic Center and the expectations it had on the political field, the public opinion and on technical branches. It is moreover absent works that details the confrontation between the newly inaugurated President Juscelino Kubitschek and Marechal José Pessoa, incumbent for the planning of the city. Bibliographic revision of local newspaper and new primary documentation shows the whereabouts of a dispute that helps to clarify Kubitschek’s pretensions for cultural power while detailing how the technical staff of Pessoa and then, Niemeyer and Costa have formulated different architectures for the square gathering the decision making palaces of the country.